The accreting Black Hole Swift J1753.5–0127 from radio to hard X-Ray - Tomsick, J.; Rahoui, F.; Kolehmainen, M.; Miller-Jones, James; Fürst, F.; Yamaoka, K.; Akitaya, H.; Corbel, S.; Coriat, M.; Done, C.; Gandhi, P.; Harrison, F.; et al. (Institute of Physics Publishing, 2015)
We report on multiwavelength measurements of the accreting black hole Swift J1753.5–0127 in the hard state at low luminosity (L ~ 2.7 × 1036 erg s−1 assuming a distance of d = 3 kpc) in 2014 April. The radio emission is optically thick synchrotron, presumably from a compact jet. We take advantage of the low extinction ( from earlier work) and model the near-IR to UV emission with a multitemperature disk model. Assuming a black hole mass of MBH = 5 M☉ and a system inclination of i = 40°, the fits imply an inner radius for the disk of Rin/Rg > 212d3(MBH/5 M☉)−1, where Rg is the gravitational radius of the black hole and d3 is the distance to the source in units of 3 kpc. The outer radius is Rout/Rg=90,000 d3(MBH/5 M☉)−1, which corresponds to 6.6 × 1010 d3 cm, consistent with the expected size of the disk given previous measurements of the size of the companion's Roche lobe. The 0.5–240 keV energy spectrum measured by Swift/X-ray Telescope (XRT), Suzaku (XIS, PIN, and GSO), and Nuclear Spectroscopic Telescope Array is relatively well characterized by an absorbed power law with a photon index of Γ = 1.722 ± 0.003 (90% confidence error), but a significant improvement is seen when a second continuum component is added. Reflection is a possibility, but no iron line is detected, implying a low iron abundance. We are able to fit the entire (radio to 240 keV) spectral energy distribution (SED) with a multitemperature disk component, a Comptonization component, and a broken power law, representing the emission from the compact jet.The broken power law cannot significantly contribute to the soft X-ray emission, and this may be related to why Swift J1753.5–0127 is an outlier in the radio/X-ray correlation. The broken power law (i.e., the jet) might dominate above 20 keV, which would constrain the break frequency to be between 2.4 × 1010 and 3.6 × 1012 Hz. Although the fits to the full SED do not include significant thermal emission in the X-ray band, previous observations have consistently seen such a component, and we find that there is evidence at the 3.1σ level for a disk-blackbody component with a temperature of eV and an inner radius of 5Rg–14Rg. If this component is real, it might imply the presence of an inner optically thick accretion disk in addition to the strongly truncated (Rin> 212Rg) disk. We also perform X-ray timing analysis, and the power spectrum is dominated by a Lorentzian component with νmax = 0.110 ± 0.003 Hz and νmax = 0.16 ± 0.04 Hz as measured by XIS and XRT, respectively.